Circularly polarized metamaterial Antenna in energy harvesting wearable communication systems - Bala Inuwa; Olabode Idowu-Bismark; Oluseun Oyeleke; Jemitola Paul Olugbeji (Institute of Advanced Engineering and Science, 2023)
When battery powered sensors are spread out in places that are sometimes hard to reach, sustaining them become difficult. Therefore, to develop this technology on a large scale such as in the internet of things (IoT) scenario, it is necessary to figure out how to power them. The proffered solution in this work, is to get energy from the environment using energy harvesting Antennas. This work presents a wearable circular polarized efficient receiving and transmitting sensors for medical, IoT, and communication systems at the frequency range of WLAN, and GSM from 900 MHz up to 6 GHz. Using a cascaded system block of a circularly polarized Antenna, a rectifier and t-matching network, the design was successfully simulated. A DC charging voltage of 2.8V was achieved to power-up batteries of the wearable and IoT sensors. The major contribution of this work is the tri-band Antenna system which is able to harvest reflected Wi-Fi frequencies and also GSM frequencies combined in a miniaturized manner. This innovative configuration is a step forward in building devices with over 80% duty cycle.